Genetics and Physiology of the Nuclearly Inherited Yellow Foliar Mutants in Soybean - Sandhu, Devinder; Coleman, Zachary; Atkinson, Taylor; Rai, Krishan M.; Mendu, Venugopal (Frontiers in Plant Science, 2018)
Plant photosynthetic pigments are important in harvesting the light energy and transfer of energy during photosynthesis. There are several yellow foliar mutants discovered in soybean and chromosomal locations for about half of them have been deduced. Viable-yellow mutants are capable of surviving with decreased photosynthesis, while lethal-yellow mutants die shortly after germination. In addition to the decreased chlorophyll content, other features associated with yellow mutants include altered Chl a and Chl b ratio, reduction in chloroplast size and number, lower levels of other photosynthetic pigments, inability of thylakoids to stack into granum, lack of lamellae to interconnect granum and reduced size of the light harvesting complex. For some yellow mutants, temperature and/or light play a critical role in the manifestation of phenotype. Although yellow foliar mutants are viewed as undesirable for crop production, there is the possibility of these mutants to create a positive impact by reducing the total amount of chlorophyll and diverting resources toward increased biochemical photosynthetic capacity leading to increased yield. Recent advances in model plants led to the isolation and characterization of various genes associated with yellow foliar phenotype. Knowledge gained from the model plants can be applied using homology based cloning approach to isolate genes in soybean and understanding the modes of actions of the involved proteins. Identifying and characterizing yellow foliar mutants will not only aid in understanding the biosynthetic pathways involved in the photosynthetic machinery, but may also provide ways to increase soybean productivity.